Cultivating Organizational Resilience through Prophetic Leadership: Empirical Insights from Islamic Schools in the Volatile Post-Pandemic Era - Ach Hafsin; Sahudi Sahudi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
This study explores the role of Prophetic Leadership in fostering organizational resilience within Islamic schools during the volatile post-pandemic era. Utilizing a qualitative phenomenological approach and a multi-site case study design, data were gathered through in-depth interviews, passive observations, and documentation analysis at several resilient Islamic institutions. The findings reveal that prophetic traits—Shiddiq (integrity), Amanah (accountability), Tabligh (communication), and Fathonah (intelligence)—collectively function as both a "value anchor" and an "innovation engine". Shiddiq and Amanah establish a foundation of trust that reduces bureaucratic friction, while Tabligh and Fathonah drive strategic communication and pedagogical innovation. Uniquely, this research identifies "Transcendental Resilience," where spiritual values transform crises into opportunities for growth, mitigating educator burnout. Theoretically, this study positions prophetic traits as pragmatic managerial competencies rather than mere theological norms. Practically, it provides a strategic framework for school leaders to maintain competitiveness and stability amidst global uncertainty.